The influence of depth of sedation on motor evoked potentials monitoring in youth from 4 to 23 years old: preliminary data from a prospective observational study - Hudec, Jan; Kosinová, Martina; Prokopová, Tereza; Zelinková, Hana; Hudáček, Kamil; Repko, Martin; Gál, Roman; Štourač, Petr (Frontiers in Medicine, 2024)
Introduction The influence of various levels of sedation depth on motor evoked potentials (MEP) reproducibility in youth is still unclear because of a lack of data. We tested the hypothesis that a deeper level of total intravenous anesthesia (TIVA) [bispectral index (BIS) 40 ± 5 compared to 60 ± 5] can affect surgeon-directed MEP and their interpretation in youths. Methods All patients received TIVA combined with propofol and remifentanil. TIVA was initially maintained at a BIS level of 60 ± 5. The sedation anesthesia was deepened to BIS level 40 ± 5 before the skin incision. MEP were recorded and interpreted at both BIS levels. The primary endpoint was to evaluate the effect of the depth of sedation on the MEP reproducibility directed and interpreted by the surgical team in each patient separately. The secondary endpoint was to compare the relativized MEP parameters (amplitude and latency) in percentage at various levels of sedation in each patient separately. We planned to enroll 150 patients. Due to the COVID-19 pandemic, we decided to analyze the results of the first 50 patients. Results The surgical team successfully recorded and interpreted MEP in all 50 enrolled patients in both levels of sedation depth without any clinical doubts. The MEP parameters at BIS level 40 ± 5, proportionally compared with the baseline, were latency 104% (97–110%) and the MEP amplitudes 84.5% (51–109%). Conclusion Preliminary data predict that deeper sedation (BIS 40 ± 5) does not affect the surgical team’s interpretation of MEP in youth patients. These results support that surgeon-directed MEP may be an alternative when neurophysiologists are unavailable.